HYDRODYNAMIC CHARACTERIZATION OF THREE PHASE FLUIDIZED BED - DRĂGAN, Simion (Studia Universitatis Babeș-Bolyai Chemia, 2015)
Hydrodynamics study plays an important role in the economical design and operation of three phase fluidized bed contactor. This paper presents the experimental investigation on the hydrodynamic behavior of a counter current gas-solid-liquid three phase fluidized bed. The results have shown that the pressure drop increases with the increase of gas velocity, spray liquid density and solid particle density. The expanded bed height increases with the increase of gas velocity and decreases with solid particles density.